Student Learning Strategies During the Covid 19 Pandemic At Binjai State Madrasah Ibtidaiyah School - Elvi Azizah; Ihsan Saraini; Rismoninta Padang; Fikri Syuhadi (Edumaspul: Jurnal Pendidikan, 2022)
Covid 19 which is endemic in Indonesia causes the learning system cannot be done face-to-face. And therefore the government has set a learning system that must be carried out by Indonesia is an online payment system. Therefore, in this study, it will be seen how the strategies that must be carried out by schools in the learning system from and what obstacles are felt by schools in the current online learning system. Is this online learning system very efficient or not very efficient in the current learning system and in this study we will also discuss the system How methods are used in learning strategies in educational institutions in Indonesia, especially at Madrasah Ibtidaiyah Negeri Binjai